Designing Flexibility, Accessibility, and Independent Learning through the Use of Hyperapp Blended Learning Module - Mansur, Hamsi; Mastur; Monry Fraick Nicky Gillian Ratumbuysang; Fitria Yuniarti (Universitas Veteran Bangun Nusantara, 2024)
The quality of e-learning is determined by two factors, learning resources and the learning processes. However, sometimes the main factor behind the low quality of e-learning is the lack of teachers in creating the learning process. E-learning ranges from